PENGARUH RETURN ON ASSETS, NON-PERFORMING LOAN, CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP HARGA SAHAM (Media Riset Akuntansi, 2022)
This study aims to determine the effect of return on assets, non-performing loans, capital adequacy ratio and loan to deposit ratio on stock prices. The sample of this research is 160 and consists of banking companies listed on the IDX during the 2017-2020 period. The method used in this research is multiple linear regression analysis. The results showed that return on assets had a positive effect on stock prices, non-performing loans had no effect on stock prices, capital adequacy ratios had a positive effect on stock prices and loan to deposit ratios had no effect on stock prices.